Biogenic Synthesis of Silver Nanoparticles (AgNPs) using Celosia cristata L. Leaves Extract and Their Antimicrobial Activity against Otorhinolaryngological Isolated Pathogen (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
This work focused on the biogenic synthesis of silver nanoparticles (AgNPs) by silver nitrate using Celosia cristata leaves extract in four different solvents namely petroleum ether, acetone, methanol, and water. Silver nitrate and leaves extract were used as a precursor and capping reducing agent respectively. Biogenic AgNPs were characterized and identified by UV-Vis spectrophotometer, X-ray diffraction (XRD), Field emission scanning electron microscope (FE-SEM), and energy dispersive spectroscopy (EDX). Disc diffusion method was used for antibacterial activity of AgNPs and effective antibacterial activity was shown against IS-3, IS-4, IS-6, and IS-7 as compared to a positive control (ciprofloxacin).